The Religious Dimensions of Compulsive Buying - Ayra, Rina (Implicit Religion, 2009)
This paper examines the implicit religiosity of compulsive buying. Much of the extant literature on the subject focuses on biological and/or psychological factors. I argue that the cycle of behaviour in compulsive buying, which oscillates between euphoria and depression, can be paralleled with Durkheim’s exposition of collective effervescence. In my paper I argue that many of the behaviours expressed in the cycles of compulsive buying can be described as religious, and that the sense of fulfilment striven for in the pursuit of commodity after commodity can be viewed as a desperate need to heal the self and, invariably, to find salvation. My understanding of the religious is discussed in a relationship between the sacred and the profane in the context of Durkheim and then Bataille, which leads me to the conclusion that compulsive buying is an implicitly religious activity.